THE EFFECT OF INCENTIVES, WORK ENVIRONMENT AND WORK DISCIPLINE ON TEACHER PERFORMANCE THROUGH RELIGIouSITY AS INTERVENING VARIABLES IN SMA "BAHRUL MAGHFIROH" MALANG - Haniffaturrohman Kasaif (JOSAR (Journal of Students Academic Research), 2021)
SMA Bahrul Maghfiroh Maghfiroh is a Islamic boarding school. The problem in this research area is about problem regarding teacher performance based on the incentives given so that improvements and achievements in work are not maximally fulfilled. The research aims to determine the effect of incentives, work environment and work discipline on teacher performance through religiosity as an intervening variable in SMA Bahrul Maghfiroh Malang. This research used census techniques. The statistical analysis used in this research was the path analysis approach. The results of this study were: 1). Incentives and work environment had a positive effect on religiosity while work discipline did not significantly influence religiosity. 2). Incentives and work environment had a positive effect on teacher performance, while work discipline did not have a significant effect on teacher performance 3). The religiosity variable had a positive effect on teacher performance at SMA Bahrul Maghfiroh. 4). Incentive variables, work environment and work discipline through mediation of religiosity indirectly had a positive effect on teacher performance at SMA Bahrul Maghfiroh which meant that incentives, work environment and work discipline affected teacher performance at SMA Bahrul Maghfiroh through religiosity. According to the results of this study, work discipline might be further improved so that the increase could be significant and teacher performance achievement could be achieved so that learning at SMA Bahrul Maghfiroh was better and more effective by providing appropriate incentives